Custom Tailoring Radio Tape Services - Larry A. Quinn (Journal of Applied Communications, 1972)
Recognizing the diversity of Texas agriculture and the contrasting geographical differences in Texas, we set out to establish a regular radio tape service which would have something to offer for all parts of the state.